2015
DOI: 10.1088/0268-1242/30/6/064006
|View full text |Cite
|
Sign up to set email alerts
|

Unusual charge transport and reduced bimolecular recombination in PDTSiTzTz:PC71BM bulk heterojunction blend

Abstract: Solar cells with bulk heterojunction active layers containing donor-acceptor copolymer PDTSiTzTz exhibit persistent high fill factors with thicknesses up to 400 nm. Transport and recombination in a blend of PDTSiTzTz and fullerene derivative PC 71 BM is studied using lateral organic photovoltaic structures. This material system is characterized by carrier-concentrationdependent charge carrier mobilities, a strongly reduced bimolecular recombination factor, and a negative Poole-Frenkel coefficient. The analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Several experimental observations , indicate that even when second-order kinetics is operative, the experimental rate constant (β exp ) is smaller than that estimated according to the Langevin model, β L , by two to four orders of magnitude. Previous reports have attributed this overestimation to 2D recombination in the lamellar structure of conjugated polymer, charge carrier concentration gradient within the device, local dielectric constant difference, slow dynamics of charge carrier with smaller mobility, , delocalization of opposite charges in an encounter complex, phase separation, domain purity, and back electron transfer to triplet excitons concurrent with redissociation of charge-transfer (CT) states back to free carriers. , …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several experimental observations , indicate that even when second-order kinetics is operative, the experimental rate constant (β exp ) is smaller than that estimated according to the Langevin model, β L , by two to four orders of magnitude. Previous reports have attributed this overestimation to 2D recombination in the lamellar structure of conjugated polymer, charge carrier concentration gradient within the device, local dielectric constant difference, slow dynamics of charge carrier with smaller mobility, , delocalization of opposite charges in an encounter complex, phase separation, domain purity, and back electron transfer to triplet excitons concurrent with redissociation of charge-transfer (CT) states back to free carriers. , …”
Section: Introductionmentioning
confidence: 97%
“…Deviations of experimental observations from Langevin theory were reported to occur in two ways: (i) deviation from second-order dependence on charge carrier density and (ii) discrepancy in the rate constant, each of which will be addressed below: Indeed, in many polymer–fullerene based devices, the charge-decay dynamics probed by charge extraction technique , and transient absorption spectroscopy , at open-circuit voltage , was found to exhibit approximately a third-order dependence on ρ­( t ). Therefore, in order to be consistent with the experimental data, the rate constant (β) in the Langevin model has to depend on charge density (or, equivalently, on t ). , This third-order dependence of the BMR rate on charge density has been suggested to arise as a result of either a carrier lifetime dependence on charge density, , recombination via an exponential tail of density of states (DoS), or carrier trapping in an inhomogeneous distribution of localized states. ,, Also, it was suggested that traps can sometimes enhance the dissociation of geminate pairs into free carriers but can act as recombination centers as well, leading to Shockley–Read–Hall (SRH) recombination dynamics. Several experimental observations , indicate that even when second-order kinetics is operative, the experimental rate constant (β exp ) is smaller than that estimated according to the Langevin model, β L , by two to four orders of magnitude. Previous reports have attributed this overestimation to 2D recombination in the lamellar structure of conjugated polymer, charge carrier concentration gradient within the device, local dielectric constant difference, slow dynamics of charge carrier with smaller mobility, , delocalization of opposite charges in an encounter complex, phase separation, domain purity, and back electron transfer to triplet excitons concurrent with redissociation of charge-transfer (CT) states back to free carriers. , …”
Section: Introductionmentioning
confidence: 98%